Teachers' beliefs about play in infant classes in primary schools in the Republic of Ireland - Fallon, Jacqueline (Trinity College (Dublin, Ireland). School of Education, 2015)
This thesis presents the results of a qualitative, interpretative study of teachers’ beliefs about play pedagogy in infant classes in primary schools in the Republic of Ireland. The introduction of Aistear, the Early Childhood Curriculum Framework (NCCA, 2009) has drawn renewed attention to the importance of play as a context for young children’s learning. This approach has been endorsed in Literacy and Numeracy for Learning and Life (DES, 2011), the national literacy and numeracy strategy. However, while there is little research on practice in infant classes, such evidence as exists indicates that formal teaching in infant classes is widespread.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin